The foolish tortoise - Buckley, Richard, 1938- (New York : Simon Spotlight, 2015)
A tortoise realizes the need for a shell after several scary encounters.
"First Simon Spotlight Ready-to-Read edition"--Copyright page.
Originally published with slightly different text by Picture Book Studio in 1985.
Keywords: Stories in rhyme; Turtles -- Fiction